Sekolah Ibu Cerdas: Holistic Solutions to Improve Understanding and Parenting in Stunting Prevention - Khoirunnisa, Khoirunnisa; Kurniawan, Kurniawan; Akbarsyah, Nora (Media Karya Kesehatan, 2026)
Sekolah Ibu Cerdas was a program implemented in Bojong Village, Parigi District, Pangandaran Regency, as a holistic effort to improve mothers’ understanding of balanced nutrition and parenting in preventing stunting. This community-based activity focused on educational sessions involving 41 mothers with children under five. Evaluation was conducted through nutritional status measurements using weight-for-age (W/A) and height-for-age (H/A) Z-scores, as well as a post-education questionnaire assessing mothers’ knowledge and attitudes toward stunting. Results of data collection at the time showed that most children had normal nutritional status (W/A = 85.4%) and appropriate height for age (H/A = 70.7%). The average knowledge and attitude score was 24.51, indicating a generally good understanding among participants. The program also raised awareness about the importance of the First 1000 Days of Life, balanced nutrition, and democratic parenting practices that support child development. Therefore, Sekolah Ibu Cerdas proved effective in enhancing family nutrition literacy and positive parenting as a preventive measure against stunting at the village level.Keywords: Balanced nutrition, mother empowerment, parenting, stunting.